The Probability Density Function for Wind Speed Using Modified Weibull Distribution - Suwarno Suwarno (EconJournals, 2021)
Wind speed (WS) is important information to determine the potential for wind energy in an area. Wind speed has been widely expressed by the probability density function (Pdf), one of which uses the Weibull Distribution (WD). Not all WS data can be analyzed by WD because some deficiencies need to be corrected. Modified Weibull Distribution (MWD) is proposed to improve the existing WD models. In addition, this paper also compares the performance of MWD against WD using WS data measured in Medan City. To validate the two models (WD and MWD), the coefficient of determination (R-squared) and the mean square root error (RMSE) were used. In addition, data validation tests were also carried out using Chi-square and Kolmogorov-Smirnov. The result obtained is that MWD has a more acceptable fit than WD for this case. Keywords: Wind speed, Distribution function, Weibull distribution, Modified Weibull distribution JEL Classifications: C13; C22; C36; C93; L94; Q42 DOI: https://doi.org/10.32479/ijeep.11625